ANALISIS MANAJEMEN PROGRAM PENGENDALIAN PENYAKIT MENULAR (TB) DI PUSKESMAS MAGELANG UTARA KOTA MAGELANG - Dari, Yuliana Intan Wulan; Faidati, Nur (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2025)
Tuberculosis (TB) is one of the infectious diseases that is still becoming a global health challenge, including Indonesia. Puskesmas Magelang Utara has the highest cases, namely 78 cases from 256 total cases in Magelang City in 2023. This research aimed to analyze the management of TB control program in Puskesmas Magelang Utara, in terms of planning, organizing, leadership, implementation, and monitoring. This was descriptive qualitative research. Data collected through interviews, observation, and documentation. Research showed that the TB control program has been implemented through various activities, including counseling, close contact investigation, and DOTS protocol-based treatment. Intensive education and the involvement of health cadres are key strategies in early detection and supervision of drug use. However, challenges are still faced, such as low patient awareness, cases of drug discontinuation, and a limited number of health workers. The evaluation shows the need to improve public education, cross-sector collaboration, and innovation in TB control, including the development of TB alert villages. With consistent support from all relevant parties, this program is expected to contribute to achieving the TB elimination target by 2030.